Investigation of Antiproliferative Properties of Malva neglecta Extracts - Tekin, Suat; Keser, Serhat; Keser, Fatma; Sandal, Suleyman; Turkoglu, Ismail; Karatepe, Mustafa; Turkoglu, Semra (Wiley, 2017)
[Abstract Not Available]